Isotope effect in the formation of H2 from H2CO studied at the atmospheric simulation chamber SAPHIR - R. Koppmann; E. Schlosser; R. Tillmann; T. Brauers; H. Spahn; B. Bohn; R. Wegener; S. Walter; T. Röckmann; F. Rohrer (Atmospheric Chemistry and Physics, 2010)
Formaldehyde of known, near-natural isotopic composition was photolyzed in the SAPHIR atmosphere simulation chamber under ambient conditions. The isotopic composition of the product H2 was used to determine the isotope effects in formaldehyde photolysis. The experiments are sensitive to the molecular photolysis channel, and the radical channel has only an indirect effect and cannot be effectively constrained. The molecular channel kinetic isotope effect KIEmol, the ratio of photolysis frequencies j(HCHO→CO+H2)/j(HCDO→CO+HD) at surface pressure, is determined to be KIEmol=1.63−0.046+0.038. This is similar to the kinetic isotope effect for the total removal of HCHO from a recent relative rate experiment (KIEtot=1.58±0.03), which indicates that the KIEs in the molecular and radical photolysis channels at surface pressure (≈100 kPa) may not be as different as described previously in the literature.